Pengembangan Media Virtual Field Trip Berbasis Web dengan Model PjBL untuk Literasi Lingkungan Siswa MAN - Rifqi Khoir Afdan; Syarifah Widya Ulfa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to design and examine the feasibility of a web-based Virtual Field Trip (VFT) learning media integrated with the Project Based Learning (PjBL) model on mangrove ecosystem materials to improve environmental literacy of students at Madrasah Aliyah Negeri (MAN). The method used was Research and Development (R&D), which consisted of analysis, design, development, implementation, and evaluation stages. The research subjects involved tenth-grade MAN students, with practicality and effectiveness testing conducted. The results showed that the web-based VFT media had a very high level of practicality based on students’ and teachers’ responses and was effective in improving students’ environmental literacy. Project-based learning through virtual exploration helped students understand mangrove ecosystem concepts more contextually and foster environmental awareness. In conclusion, the web-based VFT media is feasible to be used as an innovative and contextual Biology learning media to enhance environmental literacy of MAN students. Keywords: Environmental Literacy, Biology Learning Media, Project Based Learning, Virtual Field Trip